(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In this article, we will talk about the self-development of the pedagogue in educational activities and the improvement of students’ language competence. In doing so, we will also consider the approaches of the pedagogue in the system of improving language skills.